Hydrogen sensors based on gold nanoclusters assembled onto ZnO nanostructures at low operating temperature - Pichitchai Pimpang (2018)
© 2017 Elsevier Ltd and Techna Group S.r.l. In this work, the hydrogen (H 2 ) sensor performance of gold nanoclusters (Au NCs) assembled onto zinc oxide (ZnO) nanostructures films were investigated and compared to ZnO nanostructures films. ZnO nanostructures were prepared by thermal oxidation of zinc films on glass substrate at different oxidation temperatures. Au NCs were assembled onto obtained ZnO nanostructures via photoreduction of HAuCl 4 solution. The morphology of ZnO nanostructures were comprised of short rods branched into their ZnO bases. The diameters of cylindrical ZnO nanostructures increased approximately 50 to 90 nm upon increasing the oxidation temperatures. The morphology of Au NCs assembled onto ZnO nanostructures exhibited growth to encapsulate individual ZnO nanostructures as cluster−like with dimensions less than 100–150 nm. The amount of Au NCs assembly was proportion to crystallinity and materials’ stoichiometry of ZnO nanostructures. H 2 sensor performance of the films were investigated at different operating temperature in the range of 150–450 °C. It was found that optimum operating temperatures of Au NCs assembled ZnO nanostructures films were 200 °C in all cases less than that 350 °C of pure ZnO nanostructures. Au NCs assembled ZnO nanostructures films had still high H 2 sensor response at operating temperature of 150 °C. Furthermore, the sensor response of Au NCs assembled ZnO nanostructures seems to have higher than those ZnO nanostructures and their sensor response was directly proportion to amount of Au NCs. Accordingly, the enhancement of sensor response can be explained in terms of the reaction rate constant (k Oxy ) by considering the catalytic effect of Au. These results can be further explored for H 2 safety sensor in fuel cell due to the demand of high H 2 response at the low operating temperature.